Identification of a seed maturation protein gene from Coffea arabica (CaSMP) and analysis of its promoter activity in tomato - Quintero, Fabíola OCampo [UNESP]; Pinto, Layra G. [UNESP]; Barsalobres-Cavallari, Carla F. [UNESP]; Arcuri, Mariana de Lara Campos [UNESP]; Pino, Lilian Ellen; Peres, Lázaro Eustáquio Pereira; Maluf, Mirian P.; Maia, Ivan G. [UNESP] (Springer Nature, 2018)
Key message: A seed maturation protein gene (CaSMP) from Coffea arabica is expressed in the endosperm of yellow/green fruits. The CaSMP promoter drives reporter expression in the seeds of immature tomato fruits. Abstract: In this report, an expressed sequence tag-based approach was used to identify a seed-specific candidate gene for promoter isolation in Coffea arabica. The tissue-specific expression of the cognate gene (CaSMP), which encodes a yet uncharacterized coffee seed maturation protein, was validated by RT-qPCR. Additional expression analysis during coffee fruit development revealed higher levels of CaSMP transcript accumulation in the yellow/green phenological stage. Moreover, CaSMP was preferentially expressed in the endosperm and was down-regulated during water imbibition of the seeds. The presence of regulatory cis-elements known to be involved in seed- and endosperm-specific expression was observed in the CaSMP 5′-upstream region amplified by genome walking (GW). Additional histochemical analysis of transgenic tomato (cv. Micro-Tom) lines harboring the GW-amplified fragment (~ 1.4 kb) fused to uidA reporter gene confirmed promoter activity in the ovule of immature tomato fruits, while no activity was observed in the seeds of ripening fruits and in the other organs/tissues examined. These results indicate that the CaSMP promoter can be used to drive transgene expression in coffee beans and tomato seeds, thus representing a promising biotechnological tool.
Keywords: Coffee; Promoter; Seed maturation protein; Seed-specific expression; Tomato